THE IMPORTANCE OF THE CREATION AND DEVELOPMENT OF CHATGPT IN ARTIFICIAL INTELLIGENCE - Khayrullayev Muminbek (Research Focus International Scientific Journal, 2024)
The emergence of ChatGPT has attracted everyone's attention, so the use value and potential ethical challenges of AI technology have become the focus of hot discussion. This paper sorts out the value of ChatGPT applications in various industries and then puts forward some new problems about AI applications. Nowadays, people are worried that artificial intelligence will replace people's work, but no one denies that it is useful to apply artificial intelligence in different areas in the future. Therefore, this article will talk about the prospects for the future development of the application of new technologies similar to AI.